Does Differentiated Leadership Threaten Who I Am? Introducing a Self-Verification Perspective to Explain the Curvilinear Effect of Differentiated Empowering Leadership - Li, Shaolong; Liao, Shudi; Sun, Fang; Guo, Zhiwen (Frontiers in Psychology, 2019)
Based on the self-verification theory, this research proposed a multi-level model for exploring whether, how, and when differentiated leadership had curvilinear effects on relationship conflict within a team and further on team members’ counterproductive work behaviors toward individuals (CWBI). Drawing on a sample of 297 team members nested in 78 teams, we found that differentiated empowering leadership had no direct curvilinear effects on relationship conflict. However, the results showed that the team competence variance could moderate the curvilinear relationship between differentiated empowering leadership and relationship conflict. Specifically, only in teams with high competence variance among members, differentiated empowering leadership had a U-shaped effect on relationship conflict. Moreover, differentiated empowering leadership interacted with team competence variance had a downstream effect on team members’ CWBI through relationship conflict. We ended up by discussing the theoretical and practical implications of these findings.